Minimizing the loses of PV panel generation by designing an intelligent controller based on FPGA - Hamza Omran, Alaa; Raheem, Itimad; Dakhel Hussien, Ali (International Journal of Engineering and Technology, 2019)
The increasing of using of an electrical power as a power source in a large number of devices can occur a serious problem in our daily life. One of the useful power sources is PV panel which used to overcome many problems of power generation. In this paper, the PV cells model is proposed to minimize loses of PV panel power generation by designing of an intelligent tracking system based on FPGA. PSO algorithms are used to train the neural networks to control the speeds and the directions of rotations of two DC motors with the help of FPGA cart. The proposed system was implemented in MATLAB; and for the hardware part, FPGA was used for the implementation of neural networks.Â Â